2014
DOI: 10.1161/circimaging.113.001156
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Magnetic Resonance Assessment of Septal Curvature Accurately Tracks Acute Hemodynamic Changes in Pediatric Pulmonary Hypertension

Abstract: Background-This study assesses the relationship between septal curvature and mean pulmonary artery pressure and indexed pulmonary vascular resistance in children with pulmonary hypertension. We hypothesized that septal curvature could be used to estimate right ventricular afterload and track acute changes in pulmonary hemodynamics. Methods and Results-Fifty patients with a median age of 6.7 years (range, 0.45-16.5 years) underwent combined cardiac catheterization and cardiovascular magnetic resonance. The majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 40 publications
1
14
1
Order By: Relevance
“…Septal curvature was the only independent variable associated with need for PH therapy in multivariable analysis. This is consistent with prior reports which have demonstrated that CMR derived minimum septal curvature and echocardiography derived septal curvature measured at end systole are associated with elevated RV pressure [ 17 , 28 , 29 ]. In the report by Pandya et al CMR derived septal curvature correlated with mean pulmonary artery pressure and pulmonary vascular resistance in older pediatric PH patients [ 17 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Septal curvature was the only independent variable associated with need for PH therapy in multivariable analysis. This is consistent with prior reports which have demonstrated that CMR derived minimum septal curvature and echocardiography derived septal curvature measured at end systole are associated with elevated RV pressure [ 17 , 28 , 29 ]. In the report by Pandya et al CMR derived septal curvature correlated with mean pulmonary artery pressure and pulmonary vascular resistance in older pediatric PH patients [ 17 ].…”
Section: Discussionsupporting
confidence: 93%
“…Septal curvature was measured from the short axis stack at the level of the papillary muscles as previously described [ 17 ] using ImageJ (National Institutes of Health, Bethesda, Maryland, USA). A total of 8 points were placed along the LV lateral wall contoured from anterolateral to inferolateral septum and the interventricular septum contoured from RV insertion point to RV insertion point.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It may be particularly useful in situations where diagnostic indictors such as septal curvature (23) are less reliable (i.e., patients with PH related to complex congenital heart disease). Nevertheless, this was not a diagnostic cohort study and further work must be performed to evaluate true diagnostic accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Transmitral E and A wave peaks were measured from the mitral valve inflow PCMR data, allowing calculation of E/A ratio. Septal curvature was assessed using the midventricular short axis cine images, as described previously [ 19 ].…”
Section: Methodsmentioning
confidence: 99%